The Onset Lactation, Early Initiation Breastfeeding, and Frequency of Antenatal Care as Determinants of Successful Exclusive Breastfeeding in Primipara Mothers - Dian Shofiya; Sri Sumarmi; Agus Sulistyono; Bagong Suyanto; Rizky Aulia Rachma; Ade Riezma Amrina Rosyida (Amerta Nutrition)
Background: Since 2016 the City of Surabaya has provided assistance and mentoring for pregnant mothers and infants during the first 1000 days of life. This initiative aims have been to alleviate stunting on children and increase exclusive breastfeeding coverage on breastfeeding mothers. However, the target for exclusive breastfeeding coverage has yet been achieved, and the level of coverage remains low despite these efforts.